Computational modeling of 915 MHz microwave ablation: Comparative assessment of temperature‐dependent tissue dielectric models. Issue 9 (7th August 2017) - Deshazer, Garron; Hagmann, Mark; Merck, Derek; Sebek, Jan; Moore, Kent B.; Prakash, Punit
Abstract : Purpose: The objective of this study is to develop a computational model for simulating 915 MHz microwave ablation (MWA), and verify the simulation predictions of transient temperature profiles against experimental measurements. Due to the limited experimental data characterizing temperature‐dependent changes of tissue dielectric properties at 915 MHz, we comparatively assess two temperature‐dependent approaches of modeling of dielectric properties: model A‐ piecewise linear temperature dependencies based on existing, but limited, experimental data, and model B‐ similar to model A, but augmented with linear decrease in electrical conductivity above 95 °C, as guided by our experimental measurements. Methods: The finite element method was used to simulate MWA procedures in liver with a clinical 915 MHz ablation applicator. A coupled electromagnetic‐thermal solver incorporating temperature‐dependent tissue biophysical properties of liver was implemented. Predictions of the transient temperature profiles and ablation zone dimensions for both model A and model B were compared against experimental measurements in ex vivo bovine liver tissue. Broadband dielectric properties of tissue within different regions of the ablation zone were measured and reported at 915 MHz and 2.45 GHz. Results: Model B yielded peak tissue temperatures in closer agreement with experimental measurements, attributed to the inclusion of decrease in electrical conductivity at elevated temperature. The simulated transverse diameters of the ablation zone predicted by both models were greater than experimental measurements, which may be in part due to the lack of a tissue shrinkage model. At both considered power levels, predictions of transverse ablation zone diameters were in closer agreement with measurements for model B (max. discrepancy of 5 mm at 60 W, and 3 mm at 30 W), compared to model A (max. discrepancy of 9 mm at 60 W, and 6 mm at 30 W). Ablation zone lengths with both models were within 2 mm at 30 W, but overestimated by up to 10 mm at 60 W. Conclusions: The inclusion of decreased electrical conductivity above 95 °C, implemented with model B as guided by our experimental measurements, may be a good approach for approximating the dynamic changes that occur during MWA at 915 MHz. Although a step toward more effectively modeling MWA at 915 MHz, further investigation of the transition in dielectric properties with temperature and tissue shrinkage, especially at high temperatures is needed for more accurate simulations.